2004
DOI: 10.1016/j.femsec.2004.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of atrazine-degrading genetic potential and activity in three French agricultural soils

Abstract: The impact of organic amendment (sewage sludge or waste water) used to fertilize agricultural soils was estimated on the atrazine-degrading activity, the atrazine-degrading genetic potential and the bacterial community structure of soils continuously cropped with corn. Long-term application of organic amendment did not modify atrazine-mineralizing activity, which was found to essentially depend on the soil type. It also did not modify atrazine-degrading genetic potential estimated by quantitative PCR targeting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(14 citation statements)
references
References 50 publications
3
10
0
Order By: Relevance
“…Indeed, omitting the data from the first 5 days of incubation in the correlation analysis showed an improved negative correlation between lag time and log libA numbers [y ϭ Ϫ3.77 log(x) ϩ 25.90; R 2 ϭ 0.68]. Previously, Tuomi et al (27) also reported a correlation (R 2 ϭ 0.459) between nahAc gene abundance and aerobic [ 14 C]naphthalene mineralization potential, while Martin-Laurent et al (14) found discrepancies between the number of atz genes and the atrazinemineralization lag times.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…Indeed, omitting the data from the first 5 days of incubation in the correlation analysis showed an improved negative correlation between lag time and log libA numbers [y ϭ Ϫ3.77 log(x) ϩ 25.90; R 2 ϭ 0.68]. Previously, Tuomi et al (27) also reported a correlation (R 2 ϭ 0.459) between nahAc gene abundance and aerobic [ 14 C]naphthalene mineralization potential, while Martin-Laurent et al (14) found discrepancies between the number of atz genes and the atrazinemineralization lag times.…”
Section: Resultsmentioning
confidence: 97%
“…These detection limits are superior or comparable to those of other SYBR green-based qPCRs targeting organic pollutant catabolic genes. Martin-Laurent et al (14) reported detection limits of 10 copies l of reaction volume Ϫ1 or 4.0 ϫ 10 3 copies g of soil Ϫ1 for the detection of atzA, atzB, and atzC. Other reported detection limits range from 80 copies g of soil Ϫ1 (1) to 2.0 ϫ 10 2 copies l of reaction mixture Ϫ1 (2).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on these data, a method was developed and published that has been shown to provide good quantity and quality DNA [65]. In addition to good reproducibility, the method provided results for DNA extraction from diverse environmental samples, including soils from a range of origins and different physical and chemical characteristics [17,59,64,79,85]. Accordingly, this method was proposed in 2006 by the Agence Française pour la Normalisation (AFNOR) to the International Organization for Standardization (ISO).…”
Section: Initial Attempts For Dna Isolationmentioning
confidence: 99%